The Faddeev-Jackiw approach and the conformal affine sl(2) Toda model coupled to the matter field - Blas, H. S.; Pimentel, B. M. (Academic Press Inc., 2000)
The conformal affine sl(2) Toda model coupled to the matter field is treated as a constrained system in the context of Faddeev-Jackiw and the (constrained) symplectic schemes. We recover from this theory either the sine-Gordon or the massive Thirring model, through a process of Hamiltonian reduction, considering the equivalence of the Noether and topological currrents as a constraint and gauge fixing the conformal symmetry. (C) 2000 Academic Press.